Quantification of chlorophyll-a, chlorophyll–b and pheopigments-a in lake sediments through deconvolution of bulk UV-VIS absorption spectra, links to files - Andrea Sanchini (PANGAEA, 2020)
Assessments of aquatic paleoproduction and pigment preservation require accurate identification and quantification of sedimentary chlorophylls. Using chromatographic techniques to analyze long records at high-resolution is impractical because they are expensive and labor intensive. We have developed a new rapid and low-cost approach to infer the concentrations of chlorophyll-a, chlorophyll-b and related chlorophyll derivatives (pheopigments-a) from the mathematical decomposition of UV-VIS measured bulk spectrophotometer absorption spectra of standards and sediment extracts. We validated our method against high-performance liquid chromatography (HPLC) measurements on standard solutions and on varved, anoxic sediment from eutrophic Lake Lugano (Ponte Tresa sub-basin, southern Switzerland), where the history of productivity is relatively well known for the 20th century. Our mathematical approach quantifies the concentration of chlorophyll-b (R_(ad_J)^2=0.99; RMSEP~5.9%), chlorophyll-a (R_(ad_J)^2=0.98; RMSEP~5.0%), and pyropheophorbide-a (R_(ad_J)^2=0.99; RMSEP~7.8%) in standard solutions. We obtain comparable results for total chloropigment-a (chlorophyll-a + pheopigments-a), chlorophyll-a and diagenetic products (pheopigments-a) in the sediment samples of our case study (Ponte Tresa). Here, concentrations of chl-b were too low. The pigment stratigraphy of the Ponte Tresa sediments correspond very well with the paleoproduction and eutrophication history of the 20th century. The ratio between chlorophyll-a and pheopigments-a used as a qualitative indicator of sedimentary chlorophyll preservation (chlorophyll-a / chlorophyll-a + pheopigments-a brace) is only weakly correlated with aquatic paleoproduction (radj= 0.35, p-value=0.045) and remained remarkably constant in the recent century despite strong anthropogenic eutrophication. The new method is useful for obtaining, in a cost- and time-efficient way, information about major sedimentary pigment groups which are relevant to infer paleoproduction, potentially green algae biomass, pigment preservation and early diagenetic effects.